What Can Count As Critical Academic Literacy Education? - Filippos Tentolouris (National Research University Higher School of Economics, 2023)
Background and Purpose: The issue of what can count as "critical" in relation to academic literacy education has not been discussed in detail in relative review studies. Therefore, this opinion article aims to contribute to this issue by exploring the question whether a field of academic literacy education can be underpinned. Approach: First, I revisit some models of academic literacy education (rhetorical models of critical consciousness, models of critical language awareness, genre-based models, multiliteracies, ethnographic-based academic literacies) which have been considered as "critical" in taxonomies of these review studies. Then, I compare these models showing their similarities and differences regarding what is "critical" and how it is situated within academic literacy education. Conclusion: Finally, I argue that since there are contrasting conceptualisations among these models in relation to what is "critical" and how it can be associated with academic literacy education, critical academic literacy education can count as a relativist and not a unified field.